Enhancing Students' Geometric Thinking Through Phase-Based Instruction Using Geometer’s Sketchpad: A Case Study - Chew , Cheng Meng (Penerbit Universiti Sains Malaysia, 2009)
I investigated Form One students’ learning of solid geometry in a phase-based instructional environment using Geometer’s Sketchpad (GSP) based on the van Hiele theory. Specifically, I examined the students’ initial van Hiele levels of geometric thinking about cubes and cuboids, and how their van Hiele levels changed after phasebased instruction with GSP. I used a case study research design and purposeful sampling to select six case study participants from a class of mixed-ability Form One students. Findings reveal that the participants’ initial van Hiele levels ranged from Level 0 to Level 2. After phase-based instruction with GSP, their van Hiele levels either increased or remained the same.